Amygdala volume changes as a potential marker of multiple sclerosis progression: links to EDSS scores and PIRA - Aleksandra Pogoda-Wesołowska; Ignacy Stachura; Nina Sługocka; Marta Kania-Pudło; Jacek Staszewski; Adam Stępień (Frontiers in Immunology)
IntroductionBrain atrophy may be a promising marker of relapsing-remitting multiple sclerosis (RRMS) progression, yet it remains underutilized in clinical practice. This exploratory study evaluated correlations between disability—as measured by the Expanded Disability Status Scale (EDSS) and progression independent of relapse activity (PIRA)—and volumetric changes in RRMS patients treated with cladribine tablets (CLAD) or alemtuzumab (ALEM).MethodsClinical and magnetic resonance imaging (MRI) data from patients with RRMS were retrospectively analyzed at four time points: pretreatment and annually over three years of follow-up. Volumetric measurements were obtained using FreeSurfer. Annual volumetric and EDSS changes were pooled together to assess short-term associations and patient-wise longitudinal analyses were performed.Results33 patients treated with CLAD and 19 patients treated with ALEM were included. Analyzing year-to-year correlations, a significant positive correlation was found between EDSS and amygdala volume changes (p = 0.00009, η²=0,15657). It was also observed for the pallidum (p=0,02605, η²=0,05384). On the contrary, a negative correlation between thalamic volume changes and EDSS in CLAD group was noted (p=0,04551, η²=0,07203).When comparing annual percentage volume changes across three groups—years with EDSS progression (n = 10), regression (n = 11), and no changes (n = 74)—significant differences were reported in amygdala (p=0,00640; 1.98%, -4%, -0.8%), thalamus (p = 0,04390; -0.54%, 2.98%, 0.1%) and pallidum (p = 0,02904; 1.98%, -6.96%, -0.23%). Finally, among the 10 patients with EDSS progression, an increase in amygdala volume was observed in 3 patients with PIRA, whereas it was not seen in the 7 patients whose EDSS progression was associated with relapsing activity (p = 0.0188; 4.60% vs. 0.004%).ConclusionOver three years of follow-up in RRMS patients, EDSS progression was positively associated with increases in amygdala—and, to a lesser extent, pallidum—volumes, while worsening disability correlated with thalamic atrophy. Notably, amygdala enlargement was exclusive to patients with PIRA versus relapse-associated worsening, highlighting its potential as a volumetric biomarker of disease progression. However it was exploratory, hypothesis-generating observation and further studies are warranted to validate these findings and elucidate the underlying mechanisms.